Peran Zakat dalam Membangun Ekonomi Berkelanjutan: Tinjauan Aksiologi Filsafat Ekonomi Islam - Pida, Dinda Fitria; Zein, Ahmad Wahyudi (Medan Resource Center, 2025)
Zakat is a key pillar in the Islamic economy that contributes to social justice and welfare. Despite its potential to support sustainable economic development, zakat management in Indonesia still faces various challenges such as low zakat collection, lack of public understanding, and transparency issues of zakat management institutions. This research aims to review the role of zakat in sustainable economic development from the axiological perspective of Islamic economic philosophy, as well as identify challenges in its management. The research method used is a literature study that reviews journals and books from 2019 to 2024. The results show that zakat can play a role in reducing poverty, economic inequality, and creating jobs, but less than optimal management hinders its positive impact. This research suggests more transparent, accountable, and community empowerment-based zakat management, as well as synergy between zakat institutions to increase its effectiveness in realizing social justice and sustainable economic development.